Peningkatan Kemampuan Kepala Madrasah dalam Menyusun Program Supervisi Pendidikan melalui Kelompok Kerja Kepala Madrasah (KKM) Berbasis Pendampingan di Madrasah Binaan - Tutik Handayani (Jurnal Kependidikan, 2018)
The purpose of this study is to describe and obtain information about the efforts of the principal's ability in preparing the program of educational supervision through the working group of principals KKM-based mentoring in MTS Binaan This research is a school action research. The research procedures in this study include planning, action, obeservation and reflection. This study consists of two cycles with four meetings. The subjects consisted of 3 headmasters of /MTS Binaan. Research data was collected using obeservation sheets. Data were analyzed using percentages. The result of the research indicates that KKM based on Mentoring can improve the ability of headmaster in preparing the education supervision program in MTS Binaan. This is evidenced by the increase in the ability of the principal in preparing the education supervision program from cycle I to cycle II. The average ability of headmaster in preparing the education supervision program in cycle I is 73.17 with enough category and in cycle II is 84.29 with good category